Confinement effect of blocks on the morphology of composite particles in co-assembly of block copolymers/homopolymers - Elmira Khaksar; Marzieh Golshan; Hossein Roghani-Mamaqani; Mehdi Salami-Kalajahi (Polyolefins Journal, 2023)
In this study, reversible addition-fragmentation chain transfer (RAFT) polymerization was used to synthesize hydrophobic polystyrene (PS), poly(methyl acrylate) (PMA), and poly(methyl acrylate-b-styrene) (PMA-b-PS) block copolymers with three distinct molecular weights. Polyaniline (PANI) was synthesized by electrochemical method. Proton nuclear magnetic resonance (1H NMR) and gel permeation chromatography (GPC) have both been used to examine the properties of the polymers synthesized. In aqueous media at room temperature, PANI has been co-assembled with PS, PMA, and PMA-b-PS. The size and morphology of the co-assembled structures have been examined using transmission electron microscopy (TEM), dynamic light scattering (DLS), and field emission scanning electron microscopy (FE-SEM). According to the findings, polymers hydrophobicity increased with increasing molecular weight, causing faster precipitation in aqueous solution and a reduction in particle size. The results demonstrated that adding conductive polymer produced core-shell morphologies, while the core morphologies are different. Thermodynamic principles governed morphology, and the most likely morphology to develop was the one that minimized the total surface free energy. The polymers caused the surface tension between the polymers with water and the surface tension between the primary polymer and the secondary polymer to be reduced by overlapping each other and precipitation.